2022
DOI: 10.1108/bpmj-05-2021-0292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supply chain performance on organizational performance mediated by customer satisfaction: a study of dairy industry

Abstract: PurposeThe aim of this study is to empirically test the relationship between supply chain performance and organizational performance mediated by customer satisfaction.Design/methodology/approachRespondents of this study include all the supply chain stakeholders, managers working in the dairy industry, bulk milk chillers/coolers (BMCs), farmer producers, wholesalers, transporters, retailers and consumers. The final sample has 67 firms and their forward and backward linkages, taking the total sample size to 1,13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…In the field of SC management literature, this study supports the previous findings of Maaz and Ahmad (2022), Lee et al . (2022), Fu et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the field of SC management literature, this study supports the previous findings of Maaz and Ahmad (2022), Lee et al . (2022), Fu et al .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the mechanism of influence in this linkage is explained by stakeholder theory as resource and capacity efforts to improve FSCS to disruption to address the concerns and interests of stakeholders by ensuring supply in terms of quantity and quality, aiming to improve business performance in a sustainable way. Previous studies found an indirect relationship between SC performance and corporate performance via customer satisfaction (Maaz and Ahmad, 2022).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…ICT has affected agility by intensifying transitional activities (Baloch et al, 2022;Maaz and Ahmad, 2022), providing transitional intelligence and substantive decision-making processes between sellers and buyers and enabling online sellers to distribute their products via virtual collaboration (Mitchell, 2021;Tang and Zhang, 2022). It heightens agility and improves online shopping mall operations (Martinez-Caro et al, 2020); promotes agility for online sellers by seeking to improve buyer transition decision-making, accelerating communication between buyer and seller relationships by delivering electronic transition process integration and providing digital transition option settings for sellers and buyers (Kessari et al, 2020).…”
Section: Organizational Performance Of the Online Sellersmentioning
confidence: 99%
“…ICT has affected agility by intensifying transitional activities (Baloch et al. , 2022; Maaz and Ahmad, 2022), providing transitional intelligence and substantive decision-making processes between sellers and buyers and enabling online sellers to distribute their products via virtual collaboration (Mitchell, 2021; Tang and Zhang, 2022). It heightens agility and improves online shopping mall operations (Martinez-Caro et al.…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%